Phosphorous fractionation distribution in surface sediments of the Jobokuto Bay - Lilik Maslukah; Anindya Wirasatriya; Muh Yusuf; Resy Sekar Sari; Ummu Salma; Muhammad Zainuri (Universitas Jenderal Soedirman, 2021)
Phosphorus (P) is an essential nutrient that can limit primary productivity in waters. Phosphorus has significant impact on the biogeochemical cycle in marine ecosystems. Surface sediments play an important role in the nutrient dynamics. Riverine input is sources of P to the ocean and sediment plays an important role as a source or sink of P in the coloumn of water. Phosphorous (P) availability is regarded as the most important factor for determining the water quality in coastal waters. However, not all of the P fractions can be released from the sediment. This study was conducted to identify the distribution of phosphorus (P) fractionation in the sediment surface of Jobokuto Bay. Samples were collected from ten locations. Percentage of sedimentary parameters such as sand, silt, clay, and organic carbon were analyzed to find out their relation with various P fractions. The sediment found was mostly sand at the station near to the coast and mud (silt and clay) at offshore stations. The results showed that Ca-P dominant (56.03%) and percentages of Fe-P, OP, and Ads-P were 23.43, 17.41, and 3.2% respectively. Terrestrial inputs and biological deposits cause Ca-P dominant. The bioavailability of P fractions were ranged from 34.45 to 56.1% of the total P (TP) content. The high concentrations of the Ads-P was found in the mud fraction and located at offshore stations. The order of abundance of the major forms of P in the surface sediments of Jobokuto bay is as follows: Ca-P > Fe-P > OP > Ads-P